Cross-sectional Method of Sugar Content and Essential Nutrients in Commercial UHT Milk for Toddlers in Indonesia - Astari Ratnaduhita; Muhammad Nur Kholis; Riska Sumirat; Choiroel Anam; Ilham Mufandi; Salman Mujahidillah Tho’at (Journal of Applied Food Technology, 2025)
UHT (Ultra High Temperature) milk is widely consumed by toddlers due to its practicality, yet concerns remain regarding the high variability of sugar levels and the adequacy of essential nutrients in commercial products. This study aimed to evaluate the total sugar content, non-lactose sugars, main milk composition, thickening agents, prebiotic fiber, and essential fats in UHT milk marketed for children aged 1–5 years, and to assess their compliance with BPOM, WHO, and Codex Alimentarius recommendations. A cross-sectional design was applied, involving purposive sampling of 27 commercially available products from modern retail outlets. Nutrient information was collected through high-resolution documentation of nutrition labels, followed by descriptive–comparative and regulatory benchmarking analyses. The findings indicate that 70.4% of products contained excessive to high total sugar levels (>6 g/100 mL), and only 7.4% met Codex energy-based criteria. UK FSA Front-of-Pack classification similarly showed that 74.1% of products fell into the high-sugar (red) category. Composition analysis revealed substantial variation, with several products relying on water, milk solids, or reconstituted milk instead of fresh milk. Thickening agents such as maltodextrin were present in selected variants, while essential fibers including FOS, GOS, and inulin were found at 1–3 g per serving, contributing up to 15% of toddlers’ daily fiber needs. Total fat content ranged from <2.5% to 6%, and some products included essential fats such as DHA or omega-3. Overall, most UHT milk products for toddlers contained sugar levels exceeding recommended limits and showed inconsistent compliance with nutritional composition standards. Strengthening product formulation, clearer labelling, and regulatory monitoring are needed to support healthier milk choices for toddlers.